Significant parameters in the evaluation of donor lungs in single-lung cellular ex vivo lung perfusion. (6th December 2018) - Niikawa, Hiromichi; Okamoto, Toshihiro; Ayyat, Kamal S; Itoda, Yoshifumi; Hata, J Steven; McCurry, Kenneth R
Abstract: OBJECTIVES: Typically, single-lung ex vivo lung perfusion (SL-EVLP) is preferred when there is concern of contamination from the opposite lung. However, a comprehensive assessment of the SL-EVLP has not been completed. The purpose of this study is to compare the physiological parameters of SL-EVLP and double-lung EVLP (DL-EVLP) in the assessment of transplant suitability. METHODS: Seven pairs of rejected donor lungs were perfused in cellular EVLP, with a tidal volume of 6 ml/kg ideal body weight and a perfusion flow of 70 ml/kg/min. The transplant suitability of each side was judged in the DL-EVLP. Subsequently, the tidal volume and flow were reduced by half. The right SL-EVLP was maintained for 10 min by clamping the left main pulmonary artery and the bronchus. Similarly, left SL-EVLP was performed. The physiological parameters were compared between SL-EVLP and DL-EVLP. RESULTS: PO2 /FiO2 ratio was significantly lower in SL-EVLP than in DL-EVLP [182.5 (127.5–309.5) vs 311.5 (257.5–377.0) mmHg, P  < 0.001]. There was a significant correlation with a higher shunt fraction and PCO2 in the pulmonary vein in SL-EVLP when compared to DL-EVLP. There was no difference in peak inspiratory and plateau pressures between SL-EVLP and DL-EVLP. Suitable lungs ( n  = 6) were associated with better PO2 /FiO2 ratios and lower airway pressures than non-suitable lungs ( n  = 8). CONCLUSIONS: In SL-EVLP, peak inspiratory and plateau pressures have clinical utility in the assessment of the transplant suitability. It is important that PO2 /FiO2 ratio in SL-EVLP is appreciably lower than that in DL-EVLP. This discrepancy should be considered in the evaluation of the transplant suitability in SL-EVLP.